Heat Optimization in Internal Curing Process of Geopolymer Mortar by Using Steel Dust - Kusbiantoro, Andri; Nabilah, Mamat; Norbaizurah, Rahman; Doh, Shu Ing (Universiti Malaysia Pahang, 2016)
Endothermic is one of the fundamental characterics in geopolymer that involves external source of heat to activate the polymerization process to form strong hardened geopolymer. However, high temperature during curing process may lead to the drying shrinkage to the specimen and affecting the mechanical properties of hardened geopolymer. Therefore, this research investigates the effect of steel dust as partial replacement of fine aggregate towards the heating optimization of internal curing process in geopolymer mortar. Experiments was conducted by replacing 5% and 10% fine aggregates with steel dust and cured at 50 °C and 60 °C for 24 hours. After 24 hours, the hardened specimens were kept in room temperature until the testing days (1, 7 and 28 days). Based on the result, the addition of 10% steel dust in geopolymer with 60°C curing temperature had the highest compressive strength as compared to others. Nevertheless, it produced an unconventional porosity-compressive strength relationship that was caused by the disruption of dissolution and polycondensation process during geopolymerization process.